Service Management as a Practice of Diakonia: A Theological Study on the Effectiveness of Equitable Service - Tesalonika Cindy Worang (International Forum of Researchers and Lecturers, 2025)
The church's diaconal practice faces a crisis of effectiveness. The dominant model of charitable diakonia (almsgiving) has proven ineffective in addressing the root causes of poverty and structural injustice. Empirical studies show that this failure is often not due to a lack of resources, but rather a failure of strategic management and a narrow theological understanding of diaconal practice itself. This research argues that to respond to poverty effectively, the church requires a dual paradigmatic shift. First, a theological shift in service from charitable diakonia to transformative diakonia, grounded in Liberation Theology and Reformed social justice spirituality. Second, a conceptual shift in